Analisa pola perkembangan wilayah kota Medan - Sagala, Donar (Institute for Advanced Science Social, and Sustainable Future, 2024)
The growth of the population and the development of the city are interrelated. Each increase in the population has an impact on the growth of the city, and vice versa. With the increasing population, the demand for settlement land also increases. Consequently, the availability of land becomes more limited and diminishes every year. Medan city is an example of a city experiencing rapid regional growth and development due to fast population growth, leading to an increase in land requirements. The author examines the regional development of Medan city, urban spatial planning approaches, and environmental issues faced by the city's growth. The author employs a qualitative approach and utilizes qualitative descriptive techniques based on literature research. The research results indicate that the residential area of Medan city has increased by 235.94%, rising from 84.56 km2 (1989) to 199.50 km2. The city's development pattern in 1989 was leap frog development, while in 2002, it showed concentric development. From 2007 to 2018, the Medan Marelan district experienced significant development, amounting to 491.06 hectares.